X-Ray Diffraction Study of the GdMIICoO3.5 (MII = Mg, Ca, Sr, Ba) Cobaltites - Mustafin, E. S.; Kaikenov, D. A.; Pudov, A. M.; Omarov, Kh. B.; Karabekova, D. Zh.; Sarsenbaev, B. Sh. (Pleiades Publishing, 2016)
—Four compounds with the general formula GdMIICoO3.5 (MII = Mg, Ca, Sr, Ba) have been pre pared for the first time by hightemperature solidstate reactions between gadolinium(III) oxide, cobalt(II) oxide, and alkalineearth carbonates. Their crystal class and unitcell parameters have been determined by X-ray diffraction.